Combined Ipsilateral Humeral Shaft and Galeazzi Fractures Creating a Floating Elbow Variant - Patrick Lee; Allison Z. Piatek; Michael J. DeRogatis; Paul S. Issack (Case Reports in Orthopedics)
“Floating elbow” injuries of the arm traditionally represent a combination of humeral shaft and forearm fractures which require anatomic rigid open reduction and internal fixation of all fractures to allow for early range of motion exercises of the elbow. There are published variants of the floating elbow injury which include ipsilateral diaphyseal humeral fracture, proximal ulna fracture with proximal radioulnar joint disruption, and ipsilateral diaphyseal humeral fracture with elbow dislocation and both bones forearm fracture. We present the case of a 21-year-old woman whose left arm became caught between the side of a waterslide and adjacent rocks at a park. She sustained a torsional and axial loading injury to her left upper extremity resulting in ipsilateral humeral shaft and Galeazzi fractures. The combination of ipsilateral humeral shaft and Galeazzi fractures resulted in a rare floating elbow variant. Prompt open reduction and internal fixation of both fractures and early range of motion of the elbow and wrist resulted in an excellent clinical and radiographic result. Floating elbow injuries and their variants should be promptly recognized as early anatomic reduction, and rigid internal fixation can allow for good elbow function with minimization of stiffness.